a)(x-√11)²
b)(-x-√11)²
c)(-x+√11)²
d)(x+√11)²
e)(√11-x)²
f)(√11+x)²
Răspunsuri la întrebare
Răspuns de
1
a)(x-√11)² =x²-2x√11+11
b)(-x-√11)² =x²+2x√11+11
c)(-x+√11)² =x²-2x√11+11
d)(x+√11)² =x²+2x√11+11
e)(√11-x)² =11-2x√11+x²
f)(√11+x)² =11+2x√11+x²
b)(-x-√11)² =x²+2x√11+11
c)(-x+√11)² =x²-2x√11+11
d)(x+√11)² =x²+2x√11+11
e)(√11-x)² =11-2x√11+x²
f)(√11+x)² =11+2x√11+x²
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Fizică,
9 ani în urmă